2005
DOI: 10.1088/1367-2630/7/1/078
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of H2in a two-dimensional crystalline matrix

Massimo Boninsegni

Abstract: Ground-state properties and superfluidity of two-and quasi-two-dimensional solid4He C Cazorla, G E Astrakharchik, J Casulleras et al. Abstract. We have carried out extensive path integral Monte Carlo simulations of two-dimensional para-hydrogen (p-H 2 ) embedded in a crystalline matrix of alkali atoms. Our results show that, at low temperatures ( 5 K), the thermodynamically stable phase of p-H 2 is a solid, commensurate with the underlying lattice. A nonzero superfluid signal for p-H 2 is observed in simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…In order to reduce this effect, however, we worked with a rather large simulation box of typical size 50Å × 50Å (i.e., as large as the one employed in Ref. 15, where suppression of p-H 2 superfluidity in a potassium film was predicted). Also the effect of adding a third dimension in the direction that is perpendicular to the alkali metal plane could change our ρ s /ρ results.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce this effect, however, we worked with a rather large simulation box of typical size 50Å × 50Å (i.e., as large as the one employed in Ref. 15, where suppression of p-H 2 superfluidity in a potassium film was predicted). Also the effect of adding a third dimension in the direction that is perpendicular to the alkali metal plane could change our ρ s /ρ results.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%
“…In particular, GC investigated two-dimensional AM-H 2 (AM = K and Cs) systems at low temperatures (i.e., 1-4 K) employing the path integral Monte Carlo (PIMC) technique. They found that the p-H 2 equilibrium state in AM-H 2 films was a liquid of concentration ∼0.04Å −2 which became superfluid at temperatures below 1.2 K. Nevertheless, a few years later Boninsegni 15 found, using a very similar approach to GC and attempting extrapolation to the thermodynamic limit, that the hydrogen equilibrium state in K-H 2 films was a crystal commensurate with the underlying lattice of alkali metal atoms. The superfluid fraction of such a commensurate system was equal to zero as reported by Boninsegni.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Path integral Monte Carlo (PIMC) simulations of p-H 2 films adsorbed on a surface with impurities observed superfluidity for some arrangements of these impurities, 17 but these results were posteriorly questioned by other PIMC studies. 18 In a one-dimensional channel, like the one provided experimentally by narrow carbon nanotubes, it has been predicted a stable liquid phase in the limit of zero temperature. 19 The largest number of theoretical works have been devoted to the study of small clusters, both pure [20][21][22][23][24][25][26][27][28][29] and doped with impurities.…”
Section: Introductionmentioning
confidence: 97%
“…To frustrate the crystal formation and reduce the strength of the interactions it was proposed to work with a twodimensional geometry with some impurities arranged in a periodic lattice [9,10]. First results obtained within this scheme found finite superfluid densities but posterior simulations were not able to reproduce these signatures [11][12][13]. The greatest effort was devoted to the study of small clusters, both pure [14][15][16][17][18][19][20][21][22][23] and doped with impurities [24][25][26].…”
Section: Introductionmentioning
confidence: 99%